Dark Angel - Andrews, V. C. (New York Pocket Books, 1986)
When she moves to Boston to live with her wealthy grandmother, Heaven believes that she has found a place to belong and an opportunity to make something of herself until she begins to realize the terrible truth beneath the glamorous facade of her grandmother's life.
Sequel to: Heaven.
Keywords: Family problems -- Fiction; Grandmothers -- Fiction